Common Bile-Duct Mucosa in Choledochoduodenostomy Patients — Histological and Histochemical Study. Issue 1 (1988) - Eleftheriadis, E.; Tzioufa, V.; Kotzampassi, K.; Aletras, H.
Abstract : We describe the histological and histochemical changes of the common bile-duct mucosa in specimens obtained by means of peroral cholangioscopy, 1–12 years after choledochoduodenal anastomosis. Our findings — hyperplasia of the superficial epithelium, metaplastic goblet cells containing predominantly acid sialomucins, and pyloric-like gland formation containing neutral mucins — express a morphological and functional differentiation of the common bile-duct mucosa that probably facilitates its survival in a different environment. We consider that these adaptive changes may explain the uneventful long-term postoperative period of choledochoduodenostomized patients.